Prevalence and characteristics of resistant hypertension at primary clinics in Korea: a nationwide cross-sectional study. Issue 1 (December 2015) - Lee, Kwang; Na, Jin; Choi, Cheol; Lim, Hong; Kim, Jin; Kim, Eung; Rha, Seung-Woon; Seo, Hong; Oh, Dong; Park, Chang
Abstract Background Although resistant hypertension (RH) is known to be associated with higher rates of cardiovascular events than is non-RH, there are no reported data on the prevalence of RH in Korean patients. We evaluated the prevalence and characteristics of RH among hypertensive patients treated at primary clinics in Korea. Methods Between August 2010 and January 2011, 247 primary care physicians enrolled 3088 patients with essential hypertension. We acquired demographic and anthropometric data using a questionnaire, evaluated blood pressure, and conducted a variety of laboratory tests using serum and urine. RH was defined as systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg with the use of three antihypertensive agents of different classes, including a diuretic, or controlled hypertension with the use of four or more medications. Results We analyzed 3088 patients with hypertension, 48.3 % of whom were men. The mean age of patients was 64.3 ± 11.3 years and the prevalence of RH was 7.9 %. Patients with RH were more likely to be men, and to have higher waist circumference, increased blood levels of HbA1c, triglycerides, and serum creatinine, lower blood levels of high-density lipoprotein (HDL), and higher rates of current smoker, history of heart failure or coronary artery disease, and electrocardiographic left ventricular hypertrophy (LVH), than were patients with non-RH (all comparisons, P  < 0.05). In the multivariate analysis, RH was shown to be significantly associated with the following conditions: presence of electrocardiographic LVH (odds ratio [OR] 2.23, 95 % confidence interval [CI] 1.34–3.71), current smoker (OR 1.75, 95 % CI 1.27–2.40), renal impairment (OR 1.65, 95 % CI 1.23–2.22), abdominal obesity (OR 1.60, 95 % CI 1.20–2.13), and cardiovascular diseases (OR 1.50, 95 % CI 1.04–2.17). Conclusions The prevalence of RH was relatively low at primary clinics in Korea compared with the prevalence reported in other countries. RH was associated with electrocardiographically confirmed LVH, renal impairment, current smoker, abdominal obesity, and cardiovascular diseases. These are the first reported data of RH in Korea. Our findings may be helpful in the early detection and thorough clinical management of patients with RH at primary clinics.